Synthesis, characterization and catalytic application of novel cyclopalladated pyridine functionalized N-heterocyclic carbene complexes - Chiang, Minyi (2011)
In this thesis, a series of novel chiral cyclopalladated pyridine functionalized NHC complexes were synthesized via a new methodology. The catalytic abilities and the selectivities of new NHC palladacycles were tested against the allylic alkylation reaction